Advancing an African Theory of Rights and Its Potential for Quality Citizenship - Ugwuanyi, Lawrence Ogbo (Universitas Islam Indonesia, 2022)
Given the numerous instances of crisis of citizenship and state belonging which disproportionately obtain in African states in comparison with other continents of the world it becomes urgent to provide positions that address the problem. This works sets out to do this by engaging the problem of rights in Africa and looking at how it affects quality citizenship. This is because the primary goal of the state is to protect rights and properties. The work will do this by engaging the nature of rights administered in the African states. It will provide a theoretical account of how a wrong idea of rights constitutes part of the problem and why the quality of rights administered in African states should be held to be the source of the problem. It will then proceed to address the problem by formulating a theory of rights anchored on an African worldview which harbours the potential to address the problem. The theory will defend the view that rights can only be found cogent and worthy to compel loyalty to its demands if it is rooted in the values and ideals of people and that an idea of rights that is endogenous to African people will be more cogent, valuable and reliable to citizenship ethics in Africa and compel loyalty to the African state. The work applies the methods of expository analysis and intuitive deduction to arrive at its positons and postulations.